Intensitas Serangan Spodoptera frugiperda pada Fase Vegetatif pada Tanaman Jagung (Zea mays) di Sumatera Selatan - Alpian, Ego; Ardiansyah, Roni Saleh; Wulandari, Nyayu Farlania; Ichsan, MuhammadHasanul; Putri, Khairunnisa; Arsi, Arsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Alpian E, Ardiansyah RS, Wulandari NF, Ichsan MH, Putri K, Arsi A. 2021. Attack intensity of Spodoptera frugiperda in the vegetative phase of maize (Zea mays) in Sumatera Selatan. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 537-544. Palembang: Penerbit dan Percetakan Universitas Sriwijaya (UNSRI). Spodoptera frugiperda is a pest that attack corn plant which is the most destructive pest in corn cultivation in the vegetative phase, this problem caused losses to the corn farmer sector and reduces the economic side of corn farmers. This study aimed to determine the intensity of the attack of S. frugiperda larvae in the vegetative phase of maize. This research methodology refers to the literature study of several journal articles. S. frugiperda attack maize in the vegetative phase, That cause stunted growth. Symptoms of the attack caused by S. frugiperda are the presence of holes and dirt that resembles sawdust. The level of damage from S. frugiperda is said to be high in the vegetative phase and will decrease with age. It is said to be high because the larvae of S. frugiperda attack the growing point of corn plants and cause damage to the young shoots.